Research on the Correlation Relationship between Personnels from Vocational Education and Regional Industrial Economy - Fei Tan (Forest Chemicals Review)
Vocational education has the dual attributes of education and economy, which is inseparable from the transformation of economic structure and industrial adjustment and upgrading. However, the causal relationship, equilibrium relationship and variable coefficient between industrial economic development and different levels of vocational and technical education are not clear. To solve this problem, through Granger causality test and Johansen cointegration Test, this paper combs out the specific correlation between the education in higher vocational college, secondary vocational schools and technical schools and important industrial economies such as transportation, finance and real estate. It is found that the leveraging effect of vocational education on industrial economic development is significantly greater than that of industrial development on vocational education. This leveraging strength on industrial economic development is far more than the change of vocational education itself. At the same time, higher education personnels have more obvious support for knowledge intensive and technology intensive industries, while intermediate skilled personnels have stronger support for industries with large number of employees and rich levels of employment.